Creative behavior, psychopathology, and salience processing: a case–control study of Italian artists from the Florence Academy of Fine Arts - Giuseppe Pierpaolo Merola; Andrea Patti; Andrea Patti; Andrea Patti; Bernardo Bozza; Davide Benedetti; Giulia Minotti; Andrea Saverio Spagnuolo; Giulia Pitt; Vincenzo Pecoraro; Andrea Lenti; Gaia D’Anna; et al. (Frontiers in Psychology)
IntroductionCreative behavior has been associated with psychopathological traits, particularly in the psychotic spectrum. Aberrant salience, a transdiagnostic feature of psychosis vulnerability, may influence the creative process. This study aimed to investigate differences between artists and non-artists in aberrant salience, creativity, personality traits, and psychopathology.MethodsThe sample consisted of 123 adults (58 artists, 65 controls) who completed self-report measures, including the Aberrant Salience Inventory (ASI), Big Five Inventory (BFI), Obsessive Beliefs Questionnaire (OBS), Remote Associates Test (RAT), and Anagram Task (ANAG). Statistical analyses included Mann–Whitney U tests for group comparisons, Spearman correlations, and regression analyses.ResultsArtists showed significantly higher aberrant salience, openness to experience, and obsessive beliefs, with lower scores on the RAT and ANAG compared to controls. Regression analyses revealed that higher ASI scores were significantly predicted by greater Openness to experience, lower Conscientiousness and higher religiosity.DiscussionThese findings suggest that artists have a greater propensity for altered salience experiences, which may contribute to their creative endeavors. The strong association between aberrant salience and openness to experience indicates that personality traits significantly influence creative expression and psychosis vulnerability. Religiosity’s role in predicting aberrant salience highlights the impact of cultural and spiritual beliefs on perceptual experiences. By identifying these associations, this study contributes to evaluating risk populations for psychosis. Artists exhibiting high aberrant salience may represent a subgroup with heightened vulnerability, underscoring the importance of early detection and intervention strategies within creative communities.